Sustainability in Australian seafood supply chains: Identifying gaps between theory and practice - Pongpakamulnarm, Uthai; Jackson, Elizabeth (2019)
This research aims to explore the trend of sustainability policies and practices in Australian seafood product supply chains and to identify the sustainability practices of supply chain members over time. A qualitative approach to content analysis was used to collect and analyse data from the annual reports of seven Australian companies in the seafood supply chain as ranked by their market share in three categories: feed production, processing, and retailing. The data were collected from annual reports over the ten-year timeframe; analysis was conducted in NVivo12. It was found that supply chain members placed sustainability practice as their business priority. The results revealed the trend that companies have become more aware of the impact of sustainability on their business over time. The results of the data analysis show the frequencies of references of each code: “sustainability”, “traceability”, “waste management”, “quality management”, and “supply chain strategy”. The code “sustainability” accounted for the highest of frequencies whereas, despite being a dominant theme in the literature, “traceability” was less mentioned throughout the results. The value of this research lies in the identification of the gaps between theory and practice when it comes to traceability of seafood products through the supply chain.